Impact of PEGylated Liposomal Doxorubicin and Carboplatin Combination on Glioblastoma - Mohsen Ghaferi; Aun Raza; Maedeh Koohi; Warda Zahra; Azim Akbarzadeh; Hasan Ebrahimi Shahmabadi; Seyed Ebrahim Alavi (MDPI AG, 2022)
Glioblastoma is an incurable cancer with a 5-year survival chance of less than 5%. Chemotherapy is a therapeutic approach to treating the disease; however, due to the presence of the blood-brain barrier (BBB), the probability of success is low. To overcome this issue, nanoparticles are promising carriers for crossing the BBB and delivering drugs to the tumor. In this study, the anticancer efficacy of doxorubicin (DOX) and carboplatin (CB) loaded into polyethylene glycol (PEG)ylated liposome nanoparticles (PEG-Lip) and in treating brain cancer was evaluated in vitro and in vivo. The results demonstrated that PEG-Lip-DOX/CB with a size of 212 ± 10 nm was synthesized that could release the loaded drugs in a controlled manner, from which 56.3% of the loaded drugs were released after 52 h. In addition, PEG-Lip-DOX/CB could significantly increase the cytotoxicity effects of the drugs against rat glioma C6 cells (IC50: 8.7 and 12.9 µM for the drugs-loaded nanoparticles and DOX + CB, respectively). The in vivo results also demonstrated that PEGylated liposomes, compared to non-PEGylated liposomes (Lip) and DOX + CB, were more efficient in increasing the therapeutic effects and decreasing the side effects of the drugs, in which the survival times of the glioblastoma-bearing rats were 39, 35, and 30 days in the PEG-Lip-DOX/CB, Lip-DOX/CB, and DOX + CB receiver groups, respectively. In addition, the weight loss was found to be 8.7, 10.5, and 13%, respectively, in the groups. The results of the toxicity evaluation were also confirmed by histopathological studies. Overall, the results of this study demonstrated that the encapsulation of DOX and CB into PEG-Lip is a promising approach to improving the properties of DOX and CB in terms of their therapeutic effects and drug side effects for the treatment of glioblastoma.